Towards a smart glasses society? Ethical perspectives on extended realities and augmenting technologies - Tretter, Max; Hahn, Michael; Dabrock, Peter (Frontiers in Virtual Reality, 2024)
The release of Apple Vision Pro in early February and the subsequent media coverage have pushed Mixed Reality (MR) and augmenting technologies into public consciousness, raising the question of whether we are moving towards a "smart glasses society" where wearing MR-devices in public becomes commonplace, and regularly engaging with extended realities will be part of our everyday experience. This paper delves into the ethical implications of this potential development, scrutinizing the effects smart glasses may have on our humanity, our relation to the world, and our shared-life world. It calls for a nuanced approach that earnestly engages with these concerns while maintaining a composed outlook, recognizing that many of these issues discussed in the context of immersive technologies, although they seem new, have been with us for quite some time.